Numerical study of mixed bio-convection associated with a micropolar fluid. (1st August 2020) - Hashem Zadeh, Seyed Mohsen; Mehryan, S.A.M.; Sheremet, Mikhail A.; Izadi, Mohsen; Ghodrat, Maryam
Highlights: Mixed bio-convection associated with a non-Newtonian micropolar fluid is studied. 4th Runge-Kutta and the Newton–Raphson methods are employed to solve ODEs. Increasing vortex viscosity enhances the density number of the motile microorganisms. Increment of the bio-convection Lewis number reducesthe coupled stress. Increasing microorganisms concentration difference parameter (Ω) enhances the angular velocity of fluid particles. Abstract: In the present study, the nanoliquid flow, heat and mass transfer over a vertical stretching sheet under the impact of motile microorganisms are investigated, numerically. Analysis is performed using the two-component four-equation non-homogeneous equilibrium nanoliquid model. At the same time, the nanoliquid is modeled as a micropolar non-Newtonian fluid. Formulated partial differential governing equations are transformed to ordinary differential equations and solved by the fourth-order Runge-Kutta method with the iterative Newton-Raphson technique. Analysis is conducted for a wide range of control parameters and heat transfer enhancement is obtained for high values of the Richardson number, bioconvection Lewis number and bioconvection Peclet number. It has been revealed that with increasing microorganisms concentration difference parameter (Ω), the angular velocity of fluid particles slightly increases and the temperature reduces and increases with increment in Ω and the bioconvection Rayleigh number ( Rb ), respectively. The results also showed that increasing bioconvection Lewis number ( Lb ) and Peclet number ( Pe ) leads to a decrease in the coupled stress; moreover, an increment in the vortex viscosity parameter (Δ) intensifies the penetration of microorganisms from the sheet to the boundary layer and amplifies the density number of motile microorganisms.